A thermally stable inorganic perovskite film and a method for preparing the same
Through continuous phase conversion process and gradient annealing technology, high-quality inorganic perovskite films are prepared, which solves the problems of complex preparation, high cost and insufficient stability in the existing technology, and achieves efficient and stable solar cell performance.
Patent Information
- Application Number
- CN202110134718.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-02-01
AI Technical Summary
The existing inorganic perovskite film preparation technology is complex, expensive, and insufficient stability, which cannot meet the needs of commercial solar cells.
The continuous conversion process is adopted to prepare high -quality inorganic perovskite film, and obtain a dense and uniform film through gradient annealing and continuous phase transformation (α → Δ → α) process.
The photoelectric performance of the solar cell is improved, high thermal stability is achieved, the lattice tensile strain of the film is small, and there are few crystal defects, making it suitable for industrial production.
Smart Images

Figure CN112968129B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a thermally stable inorganic perovskite film and a preparation method thereof. Background Art
[0002] With the development of society and the advancement of science and technology, global electricity consumption has increased dramatically, and environmental pollution caused by the burning of fossil fuels has become increasingly serious. As a renewable clean energy source with abundant reserves, the preparation and application of solar cells based on the photovoltaic effect is an effective way to solve the energy crisis and environmental pollution problems. As the third generation of solar cells, perovskite solar cells are one of the most promising photovoltaic power generation technologies. After a short period of rapid development, the photoelectric conversion efficiency of perovskite solar cells has increased from the initial 3.8% in 2009 to the current 25.5% certified by NREL. This efficiency is completely comparable to the efficiency of traditional commercial silicon cells. However, in order to fully industrialize perovskite solar cells, it is urgent to break through some key issues, among which the biggest challenge is the stability of the battery.
[0003] A large number of studies have shown that under high temperature, oxygen and humidity conditions, the organic cation components in the system of organic-inorganic hybrid perovskite materials will undergo severe decomposition, resulting in failure of the perovskite photoactive layer, thereby reducing the performance and stability of the device. Given that the main role of organic cations is to stabilize the perovskite structure and change the lattice parameters, they have no decisive effect on the band structure of perovskite materials; and the strength of the Cs-I ion bond in inorganic perovskite materials is much greater than the HI bond in organic-inorganic hybrid perovskite materials. Therefore, using Cs + Completely replacing organic cations, the inorganic perovskite material formed is expected to solve the stability problem of perovskite solar cells. In order to make inorganic perovskite solar cells have a certain market competitiveness, it is of great significance to provide a simple and low-cost inorganic perovskite film preparation technology and use it efficiently and stably in perovskite solar cells. Summary of the invention
[0004] In order to overcome the defects of the inorganic perovskite film in the prior art, such as complex preparation, high cost, performance that cannot meet the requirements of commercial batteries, especially insufficient stability, the purpose of the present invention is to provide a thermally stable inorganic perovskite film and a preparation method thereof, as well as a battery device using the inorganic perovskite film. The present invention uses a continuous phase conversion process to prepare a high-quality inorganic perovskite film, thereby effectively improving the photoelectric performance of solar cells. The whole process is easy to operate and has high repeatability. The inorganic perovskite film prepared by the present invention has high quality, small lattice tensile strain, few crystal defects, a grain size of 5±1μm, and is densely and evenly covered on the surface of the base.
[0005] The first object of the present invention is to provide a thermally stable inorganic perovskite film, wherein the inorganic perovskite undergoes a continuous phase transition from α→δ→α and is uniformly and densely covered on the surface of a substrate, wherein the inorganic perovskite chemical formula is ABX3, wherein A is selected from Cs + , Rb + One or a combination of two of the above, preferably Cs + ; B is selected from Pb 2+ , Sn 2+ etc., or a combination of two thereof, preferably Pb 2+ ; X is selected from Cl - ,Br - , I - One or a combination of two or more of the following, preferably Br - and I - mixture.
[0006] Preferably, the ABX3 is CsPbI a Br 3-a , a is an integer between 1 and 3, such as a is 1, 2 or 3; preferably, the ABX3 is CsPbI2Br. Among the numerous inorganic perovskite materials, considering that CsPbI3 is unstable under atmospheric conditions, and the bandgap widths of CsPbIBr2 and CsPbBr3 are too large, only CsPbI2Br with a bandgap of 1.92eV and a relatively stable existence in the atmosphere has great potential for application in tandem cells and semi-transparent photovoltaic devices. As the core of perovskite solar cells, the film quality of the light-absorbing layer will determine the final photovoltaic performance of the device. Therefore, ABX3 is preferably CsPbI2Br.
[0007] Furthermore, the grain size of the inorganic perovskite is 1-10 μm, preferably 4-7 μm, and more preferably 5±1 μm. The grains of the inorganic perovskite of the present invention have few crystal defects.
[0008] The inorganic perovskite is a crude inorganic perovskite that has undergone a gradient annealing treatment and then a continuous phase transformation (α→δ→α), specifically, the crude inorganic perovskite first undergoes a phase transformation from α→δ in a high humidity environment to obtain a δ phase, and then annealed at a high temperature to undergo a phase transformation from δ→α to obtain an α phase. The α phase is a cubic system of perovskite, and the δ phase is a hexagonal system of perovskite.
[0009] The perovskite film obtained by the above-mentioned continuous phase transformation of the present invention has a relative tensile stress release of more than 40%, preferably more than 50%, and more preferably more than 55%. The relative tensile stress release is based on the stress of the powdered inorganic perovskite being 0% and the XRD peak position being A; the tensile stress of the black α phase of the crude inorganic perovskite film obtained after annealing is 100%, and the XRD peak position is B, and then the relative percentage of tensile stress release is calculated by the peak position C of the XRD of the inorganic perovskite film to be tested. The relative tensile stress release percentage calculation formula of the inorganic perovskite film to be tested is:
[0010] The XRD peak position is the main peak of the (100) crystal plane, that is, a characteristic peak near 14.6°.
[0011] Furthermore, the high humidity environment is placed in 60-90% humidity for 2-30 minutes, preferably placed in 70-80% humidity for 5-15 minutes; the high temperature annealing is annealing at 250-350°C for 1-20 minutes, preferably annealing at 260-300°C for 10-15 minutes.
[0012] In a preferred technical solution of the present invention, the ABX3 is CsPbI2Br, and the size of its crystallite is 5±1 μm. Furthermore, its XRD diffraction pattern has characteristic peaks at the following 2θ: 14.6°±0.3°, 20.9°±0.3°, 24.5°±0.3° and 29.6°±0.3°, and there are no characteristic peaks at 12.6°±0.3° and 10.2°±0.3°.
[0013] In another preferred technical solution of the present invention, the absorption edge of the inorganic perovskite is 660±30 nm.
[0014] The substrate is not particularly limited, including but not limited to silicon wafers, quartz wafers, glass wafers, high molecular polymer (PET) substrates, indium-doped tin dioxide conductive glass (ITO) wafers, fluorine-doped tin dioxide conductive glass (FTO) wafers, graphene substrates, mica wafers and various metal substrates, etc., preferably indium tin oxide conductive glass (ITO) wafers.
[0015] The second object of the present invention is to provide a method for preparing the inorganic perovskite film, comprising the following steps:
[0016] (1) preparing an inorganic perovskite precursor solution, and coating the inorganic perovskite precursor solution on a substrate surface to prepare an inorganic perovskite precursor film;
[0017] (2) subjecting the inorganic perovskite precursor film of step (1) to a gradient annealing treatment to obtain a crude inorganic perovskite film;
[0018] (3) The inorganic perovskite film of step (2) is subjected to a continuous phase transformation treatment to obtain a refined inorganic perovskite film.
[0019] Furthermore, the inorganic perovskite precursor in step (1) comprises at least one of the following components: (a) at least one compound having a structural formula of AX and at least one compound having a structural formula of BX2; (b) at least one ABX3 type inorganic perovskite material. The definitions of A, B, and X are consistent with the above inorganic perovskite chemical formula ABX3.
[0020] In the above preparation method, in step (1), the solvent of the inorganic perovskite precursor solution is an amide solvent and / or a sulfone solvent, preferably DMF and / or DMSO; the concentration of the inorganic perovskite precursor solution is 0.8-1.5M, preferably 1-1.2M.
[0021] In the above-mentioned preparation method, in step (1), the inorganic perovskite precursor thin film preparation method can be a common thin film preparation method such as spin coating, blade coating, roller coating, spray coating, printing, etc., preferably spin coating.
[0022] Preferably, the spin coating is divided into two stages, the first stage spin coating speed is 500-1500rpm, the time is 5-20s, preferably the first stage speed is 1000-1200rpm, the time is 10-15s; the second stage spin coating speed is 1000-3000rpm, the time is 1-3min, preferably the second stage speed is 1500-2000rpm, the time is 1.5-2min.
[0023] Preferably, in step (2), the gradient annealing method is divided into two steps for annealing, the first step is low-temperature fast annealing, and the second step is high-temperature slow annealing. Specifically, the first step annealing temperature is 40-60°C, the annealing time is 1-4 minutes, preferably the first step annealing temperature is 50-55°C, and the annealing time is 2-3 minutes; the second step annealing temperature is 140-180°C, and the annealing time is 5-20 minutes, preferably the second step annealing temperature is 150-160°C, and the annealing time is 10-15 minutes.
[0024] The annealing treatment in step (2) adopts a gradient annealing method to slowly evaporate the solvent in the precursor film, regulate the crystal nucleation and growth rate of the perovskite, and initially obtain a flat, dense and uniform inorganic perovskite film.
[0025] Preferably, in step (3), the continuous phase transformation treatment is to firstly undergo a phase transformation from α to δ in a high humidity environment, and then undergo annealing at a high temperature to undergo a phase transformation from δ to α. The α phase is a cubic system of perovskite, and the δ phase is a hexagonal system of perovskite.
[0026] The inorganic perovskite film obtained in step (2) is subjected to secondary treatment by continuous phase conversion technology. First, the inorganic perovskite film in step (2) is placed in a high humidity environment, and the film is converted from the black α phase to the yellow δ phase. The grain size of the film is almost unchanged, and the lattice tensile strain is reduced. The δ phase film obtained in the above is annealed at a high temperature. Then, the yellow δ phase perovskite film is heat treated at a high temperature, and the film is converted from the yellow δ phase to the black α phase. This stage is further divided into two steps, namely before and after the δ→α phase conversion. Before the phase conversion, since CsI and PbI2 or PbBr2 are both easily soluble in water, in the first stage, water molecules will interact with the exposed ions at the grain boundaries of the film. As the temperature gradually increases, the water molecules in the δ phase film are gradually released. Due to the Oswald ripening mechanism, small grains will fuse with each other to obtain a large-sized grain film. The grain enlargement mainly occurs in this process. When the temperature rises to the critical temperature of phase transition, δ→α phase transition occurs, and finally a high-quality inorganic perovskite film is obtained. The film surface is flat, without voids, the grain size is 5±1μm, and the relative tensile stress is released. Finally, a perovskite film with large crystal grain size and good crystallinity is obtained through continuous phase transition technology, and it is kept highly uniform over a large area; the large-grain perovskite film has few defects, which greatly reduces the probability of carrier recombination during transportation, and the leakage current is also reduced, thereby improving the overall performance of solar cell devices based on this film.
[0027] Furthermore, the high humidity environment is placed in 60-90% humidity for 2-30 minutes, preferably placed in 70-80% humidity for 5-15 minutes; the high temperature annealing is annealing at 250-350°C for 1-20 minutes, preferably annealing at 260-300°C for 10-15 minutes.
[0028] In the inorganic perovskite film prepared according to the above method, the perovskite grains are densely arranged, have good crystallinity, have high integrity, and the particle size on the XY plane is about 5±1 μm.
[0029] The third object of the present invention is to provide an inorganic perovskite thin film solar cell, wherein the light absorption layer of the cell adopts the above-mentioned inorganic perovskite thin film.
[0030] The inorganic perovskite thin film solar cell can be a planar structure or a mesoporous structure perovskite thin film solar cell, preferably a planar structure perovskite thin film solar cell. The planar structure perovskite thin film solar cell is composed of a conductive substrate, a dense electron transport layer, the inorganic perovskite thin film light absorption layer, a hole transport layer and a top electrode in sequence.
[0031] The conductive substrate can be a tin dioxide conductive glass doped with fluorine or indium; the dense electron transport layer can be any one of titanium dioxide (TiO2), zinc oxide (ZnO) and tin dioxide (SnO2); the hole transport layer material is selected from poly 3-hexylthiophene (P3HT), poly 3-acetic acid thiophene (PTAA), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), CuSCN and NiO x Any one of; the top electrode may be a metal material with a higher work function, including but not limited to gold, silver or conductive carbon material.
[0032] Compared with other prior arts, the present invention has the following advantages:
[0033] 1. The high-quality inorganic perovskite film prepared as disclosed in the present invention has a qualitative leap in thermal stability compared with the organic-inorganic hybrid perovskite film. The prepared perovskite film will not undergo any decomposition at 280°C, which fundamentally solves the thermal instability problem of the organic-inorganic hybrid perovskite film; in addition, the solar cell based on the prepared inorganic perovskite film achieves excellent photoelectric conversion performance and has a very high open circuit voltage, which provides important guidance for the development of semi-transparent cells and stacked cells, and is expected to be combined with perovskite cells, silicon cells, and CIGS cells to effectively improve the efficiency of stacked cells.
[0034] 2. The present invention provides a preparation technology for high-quality inorganic perovskite film and a high-performance battery device. In the preparation process of the high-quality inorganic perovskite film, a gradient annealing strategy is introduced to control the solvent evaporation rate, thereby regulating the nucleation and growth rate of the perovskite crystal, and initially obtaining a dense and flat inorganic perovskite film; then, a continuous phase conversion technology (α→δ→α phase) is further introduced to further grow the inorganic perovskite film initially obtained, and the inorganic perovskite film finally obtained has high quality, which is specifically manifested in small lattice tensile strain, few crystal defects, and a grain size of 5±1μm, which is dense and uniform. The purpose of gradient annealing is to initially obtain an α-phase perovskite film, and then obtain a higher quality α-phase perovskite film through continuous phase conversion technology. The preparation method has mild preparation conditions, simple preparation steps, convenient operation, low cost, low energy consumption, high repeatability and many other advantages, and is suitable for industrial production.
[0035] 3. The present invention also provides an inorganic perovskite solar cell. The all-inorganic perovskite solar cell adopts the above-mentioned high-quality inorganic perovskite film as a light-absorbing layer, achieves excellent photoelectric conversion efficiency, and obtains a higher open-circuit voltage. It is expected to be used as a bottom cell of a stacked cell to improve the photoelectric conversion efficiency of the stacked cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a flow chart of the continuous phase conversion process for obtaining the inorganic perovskite film in Example 1.
[0037] Figure 2 This is the X-ray diffraction spectrum of the inorganic perovskite film in Example 1.
[0038] Figure 3 (a) is a scanning electron microscope (SEM) image of the inorganic perovskite film in Example 1, Figure 3 (b) is a scanning electron microscope image of the inorganic perovskite film in Comparative Example 1.
[0039] Figure 4 The UV-visible absorption spectrum of the inorganic perovskite film in Example 1 is
[0040] Figure 5 The photoluminescence spectrum of the inorganic perovskite film in Example 1 ( Figure 5 a) and fluorescence lifetime spectra ( Figure 5 b).
[0041] Figure 6 is the JV test curve of the high performance solar cell prepared in Example 1 ( Figure 6 a) and external quantum efficiency EQE diagram ( Figure 6 b).
[0042] Figure 7 It is a relative efficiency curve of the photoelectric conversion efficiency of the solar cell assembled with the perovskite thin film obtained in Example 1 and Comparative Example 1, which is continuously operated for 800 hours at 65°C. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments and drawings.
[0044] Embodiment 1:
[0045] Select CsI, PbI2 and PbBr2 as raw materials for perovskite precursor solution, dissolve them in DMSO solvent in a molar ratio of 2:1:1, stir at 60°C for 2 hours to prepare a 1.2M inorganic perovskite precursor solution, filter it and use it. Prepare the perovskite film according to the following steps:
[0046] (1) Spin coating the inorganic perovskite precursor solution on a substrate at a spin coating rate of 1000 rpm / 10 s and 2000 rpm / 2 min to obtain a transparent perovskite precursor film.
[0047] (2) The perovskite precursor film is subjected to a gradient annealing method, specifically: first annealing at 50° C. for 2 min; then annealing at 160° C. for 10 min, to obtain a crude inorganic perovskite film.
[0048] (3) The inorganic perovskite film obtained above is placed in a 70-80% humidity environment to obtain a yellow δ-phase perovskite film, and then subjected to a secondary annealing at 280° C. for 10 min to finally prepare a refined inorganic perovskite film.
[0049] Figure 1 Schematic diagram of preparing high-quality inorganic perovskite films using the continuous phase conversion technology in the present invention.
[0050] Figure 2 (b) is the XRD diffraction pattern of the perovskite film after being placed at 250°C for 1 hour. It is found that there is basically no change, indicating that the film has no segmentation phenomenon, proving that the film prepared in Example 1 has excellent thermal stability. The X-ray diffraction curve of the inorganic perovskite film prepared in this example is as follows: Figure 2 As shown in (a), the diffraction peaks corresponding to 2(θ) of 14.65°, 20.97°, 24.54° and 29.64° represent the (100), (110), (111) and (200) crystal planes of the perovskite crystal, respectively. The remaining diffraction peaks are attributed to the substrate ITO. In addition, no diffraction peaks of PbI2 at 12.65° and yellow δ-phase perovskite at 10.2° were detected, indicating that a pure inorganic perovskite film was obtained using the method of the present invention.
[0051] Figure 3 (a) is a scanning electron micrograph (SEM) of an inorganic perovskite film that has not undergone continuous phase conversion treatment in this embodiment; Figure 3 (b) is a scanning electron microscope (SEM) of an inorganic perovskite film treated by a continuous phase conversion process. As shown in the figure, the inorganic perovskite film obtained by the continuous phase conversion technology has a grain size of 5±1μm, which is densely and evenly covered on the substrate surface to form a high-quality film.
[0052] Figure 4 FIG. 1 is a UV-visible absorption spectrum of the inorganic perovskite film in this embodiment. The absorption edge of the inorganic perovskite film is about 660nm.
[0053] Figure 5 Photoluminescence spectrum and fluorescence lifetime spectrum of the inorganic perovskite film in this example. Figure 5 In (a), the inorganic perovskite film treated by continuous phase conversion technology has a stronger fluorescence emission intensity, and the emission peak is located at 660nm; Figure 5(b) It can be seen that after the continuous phase conversion technology treatment, the fluorescence lifetime of the inorganic perovskite film increased from 77ns to 131ns. These prove that after the continuous phase conversion technology treatment, the inorganic perovskite film has less non-radiative recombination inside and the degree of recombination of photogenerated carriers is low, indicating that the film is of high quality and has few defects.
[0054] By calculating the position of the XRD characteristic peak, the strain of CsPbI2Br in powder state is defined as 0%, the relative stress of comparative example 1 is defined as 100%, and then according to the peak position, it is calculated that the relative tensile stress release of the inorganic perovskite film obtained in Example 1 reaches 59.23%.
[0055] Embodiment 2: Construction and performance testing of solar cell devices using inorganic perovskite thin films as light-absorbing layers
[0056] The ITO conductive glass was ultrasonically cleaned with ethanol, acetone, and isopropanol for 30 minutes, then dried with nitrogen, and then treated with a UV ozone cleaner for 10 minutes.
[0057] The tin dioxide solution was spin-coated on the clean ITO conductive glass by spin coating process at a rate of 4000 rpm for 20 seconds. Then the solution was annealed at 150° C. for 30 minutes to obtain an electron transport layer with a thickness of about 30 nm.
[0058] According to the method described in Example 1, a high-quality inorganic perovskite film was prepared on the above substrate as an absorption layer.
[0059] The hole transport layer P3HT was prepared on the perovskite film (absorption layer) by spin coating, with a spin coating rate of 3000 rpm and a time of 30 s; the concentration of P3HT was 10 mg / mL.
[0060] A 80 nm thick gold layer was prepared by vacuum thermal evaporation as the top electrode of the device.
[0061] The IV curve was tested using a Newport 450W Model 91150 instrument, and the external quantum efficiency IPCE curve was tested using an Enlitech QER3011 test system. During the test, a stainless steel black metal sheet was used to control the incident light area to 0.1 cm 2 The irradiation condition is the standard one sun condition (100mW / cm 2 ).
[0062] The JV curve test results of the solar cell constructed using the inorganic perovskite film prepared by the present invention as the absorption layer are as follows: Figure 6 (a) shows the external quantum efficiency EQE curve test results. Figure 6(b) As shown in the results, the photoelectric conversion efficiency of the solar cell using the perovskite film prepared by the present invention is 16.54%, and the open circuit voltage is as high as 1.36V. Under the AM1.5G standard conditions, the monochromatic light conversion efficiency is the highest at 470nm, reaching 91.54%, and the integrated current density can reach 14.35mA / cm 2 .
[0063] like Figure 7 As shown, the stability of the perovskite film obtained by the present invention was also tested. The above solar cell was able to maintain a relative efficiency of 92.4% after continuous operation for 800 hours at 65°C (the relative efficiency is the retention rate of the initial photoelectric conversion efficiency, which is calculated by dividing the photoelectric conversion efficiency obtained by the test at that time point by the initial photoelectric conversion efficiency), while the control example had only about 40% relative efficiency under the same conditions.
[0064] Embodiment 3:
[0065] The preparation method is the same as that of Example 1, except that in the continuous phase conversion process, the second phase conversion temperature is 260° C. The preparation and performance test of the solar cell device are carried out in the same manner as that of Example 2.
[0066] Embodiment 4:
[0067] The preparation method is the same as that of Example 1, except that in the continuous phase conversion process, the second phase conversion temperature is 300°C.
[0068] The preparation and performance test of the solar cell device were carried out in the same manner as in Example 2. The preparation and performance test of the solar cell were the same as in Example 2.
[0069] Embodiment 5:
[0070] The preparation method is the same as that of Example 2, except that ZnO is used as the electron transport layer, and a ZnO solution is spin-coated on the ITO at a spin coating rate of 4000 rpm for 30 seconds, and then annealed at 150° C. for 30 minutes to obtain an electron transport layer with a thickness of about 25 nm. The preparation method and test of the solar cell are the same as those of Example 2.
[0071] Embodiment 6:
[0072] The preparation method is the same as that of Example 2, except that CsPbI3 is used as the light absorbing layer of the solar cell. The preparation method and test of the solar cell are the same as those of Example 2.
[0073] Embodiment 7:
[0074] The preparation method is the same as that of Example 2, except that 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) is used as the hole transport layer, the spin coating rate is 4000 rpm, and the time is 30 s. The preparation method and test of the solar cell are the same as those of Example 2.
[0075] Comparative Example 1:
[0076] The preparation method is the same as that of Example 1, except that the inorganic perovskite film obtained in step (1) is not subjected to any subsequent treatment. The preparation method and test of the solar cell are the same as those of Example 2.
[0077] Comparative Example 2:
[0078] The preparation method is the same as that of Example 1, except that the crude inorganic perovskite film initially obtained in step (2) is not treated by continuous phase conversion technology, but is directly subjected to secondary annealing at 280° C. for 10 min. The preparation method and test of the solar cell are the same as those of Example 2.
[0079] The performance of the solar cells assembled in the above embodiments and comparative examples is shown in Table 1 below:
[0080] Table 1
[0081]
[0082] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A thermally stable inorganic perovskite film, wherein the inorganic perovskite undergoes a continuous phase transition of α→δ→α and is uniformly and densely covered on the surface of a substrate, wherein the inorganic perovskite chemical formula is ABX3, wherein: A is selected from Cs + , Rb + One or a combination of two of the following: B is selected from Pb 2+ , Sn 2+ One or a combination of two of the following: X is selected from Cl - ,Br - , I - One or a combination of two or more thereof; the thermal stability means that the inorganic perovskite film will not decompose at 280°C; The relative tensile stress release of the inorganic perovskite film is above 55%; The continuous phase transformation is that the crude inorganic perovskite first undergoes an α→δ phase transformation in a high humidity environment to obtain a δ phase, and then anneals at a high temperature to undergo a δ→α phase transformation to obtain an α phase; the high humidity environment is 60-90% humidity; the high temperature annealing is annealing at 260-300°C.
2. The inorganic perovskite thin film according to claim 1, characterized in that: X is Br - and I - mixture.
3. The inorganic perovskite thin film according to claim 1, characterized in that: The ABX3 is CsPbI a Br 3-a , a is an integer between 1 and 3.
4. The inorganic perovskite thin film according to claim 3, characterized in that: The ABX3 is CsPbI2Br.
5. The inorganic perovskite thin film according to claim 1, characterized in that: The grain size of the inorganic perovskite is 1-10 μm.
6. The inorganic perovskite thin film according to claim 5, characterized in that: The grain size of the inorganic perovskite is 4-7 μm.
7. The inorganic perovskite thin film according to claim 5, characterized in that: The grain size of the inorganic perovskite is 5±1 μm.
8. The inorganic perovskite thin film according to claim 1, characterized in that: The α→δ phase transformation occurs in a high humidity environment after being placed in a high humidity environment for 2-30 minutes; the annealing time at high temperature is 1-20 minutes.
9. The inorganic perovskite thin film according to claim 8, characterized in that: The high humidity environment is placed at 70-80% humidity for 5-15 minutes; the high temperature annealing is annealing at 260-300° C. for 10-15 minutes.
10. The inorganic perovskite thin film according to claim 4, characterized in that: The size of the inorganic perovskite film grains is 5±1 μm; its XRD diffraction pattern shows characteristic peaks at the following 2θ: 14.6°±0.3°, 20.9°±0.3°, 24.5°±0.3° and 29.6°±0.3°, and there are no characteristic peaks at 12.6°±0.3° and 10.2°±0.3°.
11. The method for preparing the inorganic perovskite thin film according to any one of claims 1 to 10, comprising the following steps: (1) preparing an inorganic perovskite precursor solution, and coating the inorganic perovskite precursor solution on a substrate surface to prepare an inorganic perovskite precursor film; (2) subjecting the inorganic perovskite precursor film of step (1) to a gradient annealing treatment to obtain a crude inorganic perovskite film; (3) The inorganic perovskite film of step (2) is subjected to a continuous phase transformation treatment to obtain a refined inorganic perovskite film.
12. The preparation method according to claim 11, characterized in that: The inorganic perovskite precursor of step (1) comprises at least one of the following components: (a) at least one compound having a structural formula of AX and at least one compound having a structural formula of BX2; (b) at least one ABX3 type inorganic perovskite material; and / or In step (1), the solvent of the inorganic perovskite precursor solution is an amide solvent and / or a sulfone solvent; the concentration of the inorganic perovskite precursor solution is 0.8-1.5M; and / or In step (2), the gradient annealing method is divided into two steps for annealing. The first step is low-temperature fast annealing, the annealing temperature is 40-60°C, and the annealing time is 1-4 minutes; the second step is high-temperature slow annealing; the annealing temperature is 140-180°C, and the annealing time is 5-20 minutes.
13. The preparation method according to claim 12, characterized in that: The solvent of the inorganic perovskite precursor solution is DMF and / or DMSO.
14. The preparation method according to claim 13, characterized in that: The first step annealing temperature is 50-55°C, and the annealing time is 2-3 minutes; the second step annealing temperature is 150-160°C, and the annealing time is 10-15 minutes.
15. An inorganic perovskite thin film solar cell, wherein the light absorbing layer of the cell adopts the inorganic perovskite thin film according to any one of claims 1 to 10.
16. The inorganic perovskite thin film solar cell according to claim 15, characterized in that: The solar cell is a perovskite thin film solar cell with a planar structure or a mesoporous structure, which is composed of a conductive substrate, a dense electron transport layer, the inorganic perovskite thin film light absorbing layer, a hole transport layer and a top electrode in sequence.
17. The inorganic perovskite thin film solar cell according to claim 16, characterized in that: The conductive substrate is a tin dioxide conductive glass doped with fluorine or indium; the dense electron transport layer is any one of titanium dioxide (TiO2), zinc oxide (ZnO) and tin dioxide (SnO2); the hole transport layer material is selected from poly 3-hexylthiophene (P3HT), poly 3-acetic acid thiophene (PTAA), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), CuSCN and NiO x Any one of; the top electrode is gold, silver or conductive carbon material.
Citation Information
Patent Citations
High-quality inorganic perovskite film, preparation method thereof and application of high-quality inorganic perovskite film to solar cells
CN107204379A